A new time‐of‐flight small‐angle scattering instrument at the Helmholtz‐Zentrum Berlin: V16/VSANS. (4th February 2014) - Vogtt, Karsten; Siebenbürger, Miriam; Clemens, Daniel; Rabe, Christian; Lindner, Peter; Russina, Margarita; Fromme, Michael; Mezei, Ferenc; Ballauff, Matthias
<x xml:space="preserve">Abstract</x> Small‐angle scattering methods have become routine techniques for the structural characterization of macromolecules and macromolecular assemblies like polymers, (block) copolymers or micelles in the spatial range from a few to hundreds of nanometres. Neutrons are valuable scattering probes, because they offer freedom with respect to scattering length density contrast and isotopic labelling of samples. In order to gain maximum benefit from the allotted experiment time, the instrumental setup must be optimized in terms of statistics of scattered intensity, resolution and accessible range in momentum transfer Q. The new small‐angle neutron scattering instrument V16/VSANS at the Helmholtz‐Zentrum in Berlin, Germany, augments neutron guide collimation and pinhole optics with time‐of‐flight data recording and flexible chopper configuration. Thus, the available Q range and the respective instrumental resolution in the intermediate and high momentum transfer regions can be adjusted and balanced to the individual experimental requirements. This renders V16/VSANS a flexible and versatile instrument for soft‐matter research.